Fundraising Strategies In The National Board Of Zakat (BAZNAS) Tana Toraja Regency (ZISWAF: Jurnal Zakat dan Wakaf, 2021)
Zakat is an obligation of a Muslim and is included in the five pillars of Islam. Zakat has a strategic role, namely helping the government handle the poor. This study describes collecting zakat funds in the Amil Zakat Agency of Tana Toraja Regency, a Muslim minority area.  In this study, the method used was qualitative where the researcher conducted direct interviews with the respondents. The results showed that the fundraising strategy at the National Amil Zakat Agency in Tana Toraja Regency was not optimal. Therefore,  the  researcher  recommends  that  Amil BAZNAS Tana  Toraja  Regency  hold a digital  fundraising  training  for  zakat.